Lacking bridges and apprehensive tensions: The impact of emotions and contextual factors on German L3 teachers’ perceptions and grammar teaching practices - Beslagic, Deni (Language teaching research : LTR, 2025)
This article reports the findings of a multiple-case study on four teachers of German as a third language (GL3) at a Swedish lower secondary school (year 7). To gain a better understanding of third language (L3) teachers’ pedagogical perceptions and practices about grammar teaching to young beginners, teacher emotions are used as a theoretical frame. The data consist of individual interviews, lesson observations and immediate post-observational oral reflections that are analysed qualitatively using thematic content analysis with narrative features. The study points out the links between emotions and contextual factors inside and outside the classroom – such as time, workload, colleagues’ teaching practices as well as the motivation and attitudes of the students – and shows how these interrelatedly have an impact on teachers’ thinking, beliefs and instructional decision-making. Also, three narratives about teaching grammar are laid out, where the teachers themselves are passionate but at the same time display apprehensive emotions in the fear of their students not liking it as much. The findings indicate that teacher emotions about grammar – such as the tension between passion and apprehension – exert important influence on L3 teachers’ grammar teaching practices and beliefs. Based on this, it is suggested that bridges are needed between grammar teaching in first language (L1) and L3, since the pedagogical content knowledge and the positive teacher emotions about grammar in teachers of GL3 might be powerful assets that colleagues of other language subjects could also benefit from.